PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP IPA SISWA KELAS V SDN 88 SINGKAWANG - Yan Cahyadi; Eti Sunarsih; Safrihady (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to (1) identify whether or not there is a difference in the understanding of science concepts in experimental classes with contextual teaching and learning learning models with classes that use direct learning models; (2) identify the effect of contextual teaching and learning learning models on the ability to understand science concepts of grade V students; (3) identify student responses to science learning using contextual teaching and learning learning models in grade V. This study used a quantitative approach with the type of quasi experiment with a non-equivalent control group design. The population in this study were all grade V students of SDN 88 Singkawang, totaling 44 people. Sampling in the study using non-probabilty sampling technique with purposive sampling type. Data collection techniques using tests and questionnaires. Data analysis techniques using two-sample t-test, effect size, and percentage of student response questionnaire. The results showed that (1) there is a difference in understanding the concept of science in classes that use contextual teaching and learning models with classes that use direct learning models, this is shown from the results of t-count 6.341 and t-table 2.080. (2) there is an effect of the contextual teaching and learning learning model on the ability to understand science concepts of SDN 88 Singkawang students, this is evidenced by the results of the effect size test which shows that the value is 1.5> 0.8 so that it is in the high category. (3) student responses show a positive response, as evidenced by the results of the percentage calculation which gets 87% with a good category.